2018
DOI: 10.1186/s13046-018-0926-9
|View full text |Cite|
|
Sign up to set email alerts
|

Andrographolide inhibits breast cancer through suppressing COX-2 expression and angiogenesis via inactivation of p300 signaling and VEGF pathway

Abstract: BackgroundAndrographolide (Andro), a diterpenoid lactone, has been used for treatment of various cancers with less adverse effects. However, the underlying mechanisms regarding its anti-tumor mechanism still remain unclear.MethodsCell viability and proliferation were measured by CCK8 and CFSE dilution assay. The localization of p50/p65 or cytochrome c was determined using confocal immunofluorescence. Streptavidin-agarose pulldown or ChIP assays were used to detect the binding of multiple transactivators to COX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(86 citation statements)
references
References 56 publications
2
84
0
Order By: Relevance
“…Thus, novel treatments are required to improve the outcomes of patients with osteosarcoma. Andrographolide has been reported to be a promising therapeutic for treatment of multiple types of cancer, with potent antitumor effects and minimal toxicity (11,29,(39)(40)(41)(42). However, little is known about the effects and biochemical mechanisms of action of andrographolide in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, novel treatments are required to improve the outcomes of patients with osteosarcoma. Andrographolide has been reported to be a promising therapeutic for treatment of multiple types of cancer, with potent antitumor effects and minimal toxicity (11,29,(39)(40)(41)(42). However, little is known about the effects and biochemical mechanisms of action of andrographolide in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Carboxyfluorescein Succinimidyl Ester (CFSE) dilution assay was employed to detect cell proliferation as described previously . Osteosarcoma cells were labeled by CFSE using the CellTrace CFSE cell proliferation kit obtained from Thermo Fisher Scientific following the manufacturer's instructions and seeded into six‐well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Carboxyfluorescein Succinimidyl Ester (CFSE) dilution assay was employed to detect cell proliferation as described previously. 21 Osteosarcoma cells were labeled by CFSE using the CellTrace CFSE cell proliferation kit obtained from Thermo Fisher Scientific following the manufacturer's instructions and seeded into six-well plates. After being cultured overnight, the labeled cells were stimulated with BD for 24, 48, or 72 hours, and cell proliferation index was detected and analyzed by flow cytometry (BD Biosciences).…”
Section: Cell Proliferation Analysismentioning
confidence: 99%
“…), mangiferin (Núñez Selles, Daglia, and Rastrelli 2016), voacangine (Y. Kim, Jung, and Kwon 2012), quinic acid (Singh, Chauhan, and Tripathi 2018), andrographolide (Peng et al 2018), luteolin (Cook 2018), apigenin (Yan et al 2017), rutin (Khan et al 2019), and gallic acid (Liu et al 2012) are already reported for their anticancer activities. This suggests that the screening process from the traditionally used medicinal plants contain both potential anticancer properties.…”
Section: Cell Cycle Regulatory Genes Are Targeted By Identified Activmentioning
confidence: 99%